Data phase shift for direct beam entering the interferometer - Stalin Beltran (22512557) (2025)
This works measures the wavelength of light from a moving source, with the condition of no-reflection allowed in the direct path from the source to the long path of an unbalanced the Michelson interferometer. It was found that the values do not correspond with the values expected assuming the constancy of the speed of light. However, due to noise, the setup must be redesigned in order to get a better signal to noise ratio, and more data should be collected.